Shadow Banking and the Four Pillars of Traditional Financial Intermediation - Emmanuel Farhi; Jean Tirole (ifo Institute - Leibniz Institute for Economic Research at the University of Munich, 2018)
Traditional banking is built on four pillars: SME lending, access to public liquidity, deposit insurance, and prudential supervision. This paper unveils the logic of the quadrilogy by putting core services to "special depositors and borrowers" at the heart of the analysis, and makes room for bank and depositor implicit and explicit guarantees. It analyzes how prudential regulation must adjust to the emergence of shadow banking. The model also rationalizes ring fencing between regulated and shadow banking and the sharing of liquidity in centralized platforms to counter syphoning and financial contagion.
Keywords: 330